Paid sick leave and preventive health care service use among U.S. working adults - DeRigne, LeaAnne; Stoddard-Dare, Patricia; Collins, Cyleste; Quinn, Linda (Preventive medicine, 2017)
Managing work and health care can be a struggle for many American workers. This paper explored the relationship between having paid sick leave and receiving preventive health care services, and hypothesized that those without paid sick leave would be less likely to obtain a range of preventive care services. In 2016, cross-sectional data from a sample of 13,545 adults aged 18–64 with current paid employment from the 2015 National Health Interview Survey (NHIS) were examined to determine the relationship between having paid sick leave and obtaining eight preventive care services including: (1) blood pressure check; (2) cholesterol check; (3) fasting blood sugar check; (4) having a flu shot; (5) having seen a doctor for a medical visit; (6) getting a Pap test; (7) getting a mammogram; (8) getting tested for colon cancer. Findings from multivariable logistic regressions, holding 10 demographic, work, income, and medical related variables stable, found respondents without paid sick leave were significantly less likely to report having used six of eight preventive health services in the last 12months. The significant findings remained robust even for workers who had reported having been previously told they had risk factors related to the preventive services. These findings support the idea that without access to paid sick leave, American workers risk foregoing preventive health care which could lead to the need for medical care at later stages of disease progression and at a higher cost for workers and the American health care system as a whole. •Paid sick leave is investigated as an enabling factor to receiving preventive health services.•Workers without paid sick leave were less likely to have received preventive health services.•Workers without paid sick leave were less likely to have received a flu shot.•Workers without paid sick leave were less likely to have had a pap smear.